Validation of the Physics E-Module Based on Problem Based Learning as Independent Teaching Material to Improve Critical Thinking Skills of Class XI High School Students - Riza Azriyanti; Syafriani (Postgraduate, University of Mataram, 2023)
Students' critical thinking skills are very useful and useful as preparations for facing current and future life, but the reality in the field is that students' critical thinking skills are still low. So one solution is to develop e-modules based on problem based learning. This research aims to determine the level of validity of problem based learning-based e-modules as independent teaching materials to improve the critical thinking skills of class XI high school students. The development model used is ADDIE. The instrument used in this research was a validation questionnaire by 3 validators. The data analysis technique used is the Aiken'V formula. The e-module validation results obtained an average of 0.93 with a valid category. So it can be concluded that the physics e-module based on problem based learning to improve students' critical thinking skills is valid and suitable for use in learning at school.